Penerapan Paten Sejak UU Paten No. 6 Tahun 1989 hingga UU Paten No. 13 Tahun 1997; Fengalaman Indonesia Selama Ini - Insan Budi Maulana (Jurnal Hukum IUS QUIA IUSTUM, 1999)
Since the enactment of Patent Law 1989 No. 6 until March 1998, there had been 21.761 patent applications received by the Indonesian Patent Office, and only 3% of which had been domestic applications. These had not been significant if compared tosome other countries like Japan which has its patent applications as many as 300.000 animally. Does it indicate the law capability of Indonesian people to conduct patent able inventions and innovations? Does it only mean the law consciousness of Indonesian inventors to have their technological inventions patented? Does it merely imply the economic factors?